2019
DOI: 10.1136/archdischild-2019-317124
|View full text |Cite
|
Sign up to set email alerts
|

Starting school: educational development as a function of age of entry and prematurity

Abstract: Objective To estimate the impact on early development of prematurity and summer birth and the potential 'double disadvantage' created by starting school a year earlier than anticipated during pregnancy, due to being born preterm. Design, setting and patients We investigated the impact of gestational and school-entry age on the likelihood of failing to achieve a 'Good Level of Development' (GLD) on the Early Years Foundation Stage Profile in 5-year-old children born moderateto-late preterm using data from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Furthermore, this study also found that compared with the lower grades, SE, AL, and AL/CR in female students who were in higher grades of the same age changed more over two years and the total time spent on near work increased, but there was no such difference among male students. The increase in near working hours makes them more likely to develop myopia [ 32 ]. With higher incidence and prevalence as reported in this study, female students appear to be at greater risk than male students.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study also found that compared with the lower grades, SE, AL, and AL/CR in female students who were in higher grades of the same age changed more over two years and the total time spent on near work increased, but there was no such difference among male students. The increase in near working hours makes them more likely to develop myopia [ 32 ]. With higher incidence and prevalence as reported in this study, female students appear to be at greater risk than male students.…”
Section: Discussionmentioning
confidence: 99%
“…Not all children enter school exhibiting the same skills or readiness to learn (Claessens & Engel, 2013), with a myriad of contributing factors (e.g. Duncan & Magnuson, 2011;Isaacs & Magnuson, 2011;Pettinger et al, 2019;Ziol-Guest & McKenna, 2013). School readiness is therefore a topic of great interest for both researchers and policymakers (Davies et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the literature have demonstrated an association between preterm birth and poorer cognitive outcome 10 12 . This trend was replicated in our smaller dataset where we observed a positive association between cognition at four and gestational age at birth.…”
Section: Discussionmentioning
confidence: 99%